Bisphenol-S and Bisphenol-F alter mouse pancreatic β-cell ion channel expression and activity and insulin release through an estrogen receptor ERβ mediated pathway. (February 2021) - Marroqui, Laura; Martinez-Pinna, Juan; Castellano-Muñoz, Manuel; dos Santos, Reinaldo S.; Medina-Gali, Regla M.; Soriano, Sergi; Quesada, Ivan; Gustafsson, Jan-Ake; Encinar, José A.; Nadal, Angel
Abstract: Bisphenol-S (BPS) and Bisphenol-F (BPF) are current Bisphenol-A (BPA) substitutes. Here we used pancreatic β-cells from wild type (WT) and estrogen receptor β (ERβ) knockout (BERKO) mice to investigate the effects of BPS and BPF on insulin secretion, and the expression and activity of ion channels involved in β-cell function. BPS or BPF rapidly increased insulin release and diminished ATP-sensitive K + (KATP ) channel activity. Similarly, 48 h treatment with BPS or BPF enhanced insulin release and decreased the expression of several ion channel subunits in β-cells from WT mice, yet no effects were observed in cells from BERKO mice. PaPE-1, a ligand designed to preferentially trigger extranuclear-initiated ER pathways, mimicked the effects of bisphenols, suggesting the involvement of extranuclear-initiated ERβ pathways. Molecular dynamics simulations indicated differences in ERβ ligand-binding domain dimer stabilization and solvation free energy among different bisphenols and PaPE-1. Our data suggest a mode of action involving ERβ whose activation alters three key cellular events in β-cell, namely ion channel expression and activity, and insulin release. These results may help to improve the hazard identification of bisphenols. Graphical abstract: Image 1 Highlights: Low doses of BPS and BPF enhanced glucose-stimulated insulin secretion, a key characteristic in blood glucose homeostasis. These effects seem to be due to changes in activity and gene expression of ion channels. The potency of BPS was significantly higher compared to BPF. The Estrogen Receptor (ER) β mediated bisphenols effects via an extranuclear-initiated pathway. The ERβ extranuclear-initiated pathway may start a molecular event whose activation leads to alteration of β-cell function.